System of Geography for the Use of Schools: Illustrated with More than Fifty Cerographic Maps, and Numerous Wood-Cut Engravings - Harper Brothers (Publishers) zob. Harper and Brothers; Harper & Brothers; Harper's (Publishers) zob. Harper and Brothers; Harper & Brothers Publishers zob. Harper and Brothers; Harper Brothers (Publishing) zob. Harper and Brothers; Harper and Brothers zob. Harper and Brothers (Published by Harper & Brothers, 1852)
Przedmowa s. 5.
by Sidney E. Morse, A. M. ; published by Harper and Brothers.
Keywords: Tektonika; w kartografii; Świat; Kartografia; atlasy szkolne; Berberowie; Afryka; Austria; New Jersey (Stany Zjednoczone; stan); Półkula Zachodnia; Karolina Północna (Stany Zjednoczone; stan); Missisipi (Stany Zjednoczone; stan); Persja; Rhode Island (Stany Zjednoczone); Gwatemala; Michigan (Stany Zjednoczone; stan); Arkansas (Stany Zjednoczone; stan); Pensylwania (Stany Zjednoczone; stan); Turcja; Alabama (Stany Zjednoczone; stan); Maryland (Stany Zjednoczone; stan); Ameryka Północna; Massachusetts (Stany Zjednoczone; stan); New Hampshire (Stany Zjednoczone; stan); Prusy; Francja; Grecja; Vermont (Stany Zjednoczone; stan); Nowa Anglia (Stany Zjednoczone); Algieria; Szwajcaria; Palestyna; Półkula Wschodnia; Nowy Jork (Stany Zjednoczone; stan); Azja Mniejsza; Libia; Półkula Południowa; Floryda (Stany Zjednoczone; stan); Karolina Południowa (Stany Zjednoczone; stan); Maine (Stany Zjednoczone; stan); Belgia; Illinois (Stany Zjednoczone; stan); Szkocja (Wielka Brytania); Teksas (Stany Zjednoczone; stan); Włochy; Półkula Północna; Azja; Etiopia; Iowa (Stany Zjednoczone; stan); Missouri (Stany Zjednoczone; stan); Kentucky (Stany Zjednoczone; stan); Anglia (Wielka Brytania); Hiszpania; Nowa Funlandia (Kanada); Nowa Szkocja (Kanada); Niemcy; Nubia; Arabia Saudyjska; Indiana (Stany Zjednoczone; stan); Walia (Wielka Brytania); Indie; Ohio (Stany Zjednoczone; stan); Connecticut (Stany Zjednoczone; stan); Pacyfik (region); Egipt; Wielka Brytania; Stany Zjednoczone; Delaware (Stany Zjednoczone; stan); Tennessee (Stany Zjednoczone; stan); Nowy Brunszwik (Kanada); Kalifornia (Stany Zjednoczone; stan); Georgia (Stany Zjednoczone; stan); Afryka Północna